2020
DOI: 10.1093/icvts/ivaa066
|View full text |Cite
|
Sign up to set email alerts
|

Is aortic valve replacement with a minimally invasive extracorporeal circuit a contemporary option for octogenarians?

Abstract: Abstract OBJECTIVES Minimally invasive extracorporeal circuits have been introduced to cardiac surgery in an attempt to reduce the negative effects of cardiopulmonary bypass on patient outcome. On the other hand, transcatheter aortic valve replacement (TAVR) provides an excellent option to replace the aortic valve without the need for cardiopulmonary bypass. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This study confirmed previous results from other large series of patients undergoing complex procedures, which also showed 100% technical feasibility and a low cumulative conversion rate of 2%. 9,10,55 In light of this data, we can postulate that use of modular (type IV) MiECC secures safety and ensures technical feasibility in all cardiac surgical procedures. Modular configuration permits immediate conversion to an open circuit; thus, it ultimately creates a "safety net" that eliminates any safety concern regarding air handling and volume management, while it overcomes any unexpected intraoperative scenario.…”
Section: Modular Systemsmentioning
confidence: 95%
See 3 more Smart Citations
“…This study confirmed previous results from other large series of patients undergoing complex procedures, which also showed 100% technical feasibility and a low cumulative conversion rate of 2%. 9,10,55 In light of this data, we can postulate that use of modular (type IV) MiECC secures safety and ensures technical feasibility in all cardiac surgical procedures. Modular configuration permits immediate conversion to an open circuit; thus, it ultimately creates a "safety net" that eliminates any safety concern regarding air handling and volume management, while it overcomes any unexpected intraoperative scenario.…”
Section: Modular Systemsmentioning
confidence: 95%
“…This study confirmed previous results from other large series of patients undergoing complex procedures, which also showed 100% technical feasibility and a low cumulative conversion rate of 2%. 9,10,55…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations